INCREASING DOSES OF CATTLE MANURE FOR ORGANIC CHILI PEPPER PRODUCTION (REVISTA DE AGRICULTURA NEOTROPICAL, 2020)
There is a contemporary trend of change in the agricultural sector, aiming at the use of ecologically friendly inputs. This trend can be seen by the constant increase in the demand for organic products. However, as with other technologies, there is a need for studies to evaluate the effectiveness of its use. The present study aimed to evaluate the effects of the application of increasing doses of cattle manure on the development and productivity of chili peppers. The treatments consisted of increasing doses of cattle manure (0; 5; 10; 15; 20 Mg ha-1). The variables plant height, stem diameter, number of plant leaves and length, diameter, and fruit yield were evaluated. It was found that, with the maximum amount of cattle manure, there was an increase of 35.96%, 41.12%, 47.84%, and 161.64% concerning the control treatment, without the cattle manure application. Thus, it was concluded that the use of increasing doses of cattle manure, up to 20 Mg ha-1, is beneficial to the development and production of chili pepper.